2019
DOI: 10.1080/13608746.2019.1644809
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Coalitions and Policy Reversals in Portugal and Italy in the Aftermath of the Eurozone Crisis

Abstract: This paper links patterns of deregulatory reforms and postcrisis reversals in Italy and Portugal with the electoral constituencies of political parties. Combining insights from the social coalitions and electoral behaviour debates, we link reform outcomes to the class setup of the electorate in the two countries by using the class schema developed by Daniel Oesch. We find that governments in both countries reversed austerity measures in order to protect core groups of voters within their electorate in spite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…This is confirmed by the articles in this volume, which show that reversals are a common occurrence in the aftermath of the crisis; but that governments are selective in their choices. The contributions of Branco et al (2019), Afonso and Bulfone (2019) and show that reversals are observed across all policy areas, by both the left and the right, and in all countries. For example, Branco et al (2019) count a total of 17 reversals of structural reforms: five in Spain, and six each in Portugal and Italy.…”
Section: Reversals In Spain Portugal Italy and Greecementioning
confidence: 89%
See 4 more Smart Citations
“…This is confirmed by the articles in this volume, which show that reversals are a common occurrence in the aftermath of the crisis; but that governments are selective in their choices. The contributions of Branco et al (2019), Afonso and Bulfone (2019) and show that reversals are observed across all policy areas, by both the left and the right, and in all countries. For example, Branco et al (2019) count a total of 17 reversals of structural reforms: five in Spain, and six each in Portugal and Italy.…”
Section: Reversals In Spain Portugal Italy and Greecementioning
confidence: 89%
“…Another similarity with Portugal's neighbour is that new job creation compensated for only half of the job losses during the crisis; and part time employmentwhich was almost nonexistent in 2008reached nine per cent in 2017 (one third of which is involuntary). Despite this relative lack of success of the internal devaluation strategies, most of the labour markets reforms were kept, with the exception of measures on the extension of collective agreements (that was requested by employers) and on extra working hours in the private sectorwhich had the agreement of employers and the smaller trade unions (Afonso & Bulfone 2019).…”
Section: Reversals In Spain Portugal Italy and Greecementioning
confidence: 99%
See 3 more Smart Citations